Legal Certainty Of Requests For Suspension Of Debt Payment Obligations Against Insurance Companies Defaulting On Payment (Journal of Namibian Studies : History Politics Culture, 2023)
Insurance companies defaulting on payment have a special scheme to file for bankruptcy or request for suspension of debt payment obligations (Penundaan Kewajiban Pembayaran Utang or PKPU). In this case, the authorized entity is the the Financial Services Authority (Otoritas Jasa Keuangan or OJK). Creditors can only apply to the OJK to consider the eligibility of an insurance company to be declared bankrupt or receive PKPU. However, in reality, a court decision on case number 389/Pdt.Sus-PKPU/2020/PN Niaga Jkt.Pst. at the request of PKPU issued by creditors (insurance policyholders). This case led the authors to conduct a study to analyze the reasons for requests for the suspension of debt payment obligations (PKPU) against insurance companies that pay back filed by the OJK only, and analyze the legal certainty of PKPU requests submitted by customers against insurance. companies that fail to pay based on the Court's Decision on Case No. 389/Pdt.Sus-PKPU/2020/PN Niaga Jkt.Pst. The research method was the normative law method, which refers to a literature review aimed to obtain secondary data. The results of the study show that the role of the OJK as the authorized entity in managing bankruptcy requests against insurance companies to increase public trust towards insurance companies is not solely to bankrupt the company. There has been a legal uncertainty when the Panel of Judges of the Commercial Court granted the PKPU request submitted by creditors against PT Asuransi Jiwa Kresna (Kresna Life).